PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH (MAM) TERHADAP HASIL BELAJAR KOGNITIF DAN MOTIVASI PESERTA DIDIK - Saniatur Rohmah; Ni Made Dwi Widyastuti; Apriani Sulu Parubak; Christiana Niken Larasati (Universitas Papua, Manokwari, Indonesia, 2019)
AbstractThis study aims to determine whether there are differencas in cognitive dan motivation students’ learning out comes or to determine the percentage effect of using coooperative learing model Make A Match (MAM) X grade in SMK Negeri 2 Manokwari the study usen quasi exsperimental method. This study was conducted during three meetings, inckuding pretest before taeching the subject andthe postest after taching the subject. This research began on februari to may 2016. The sample of this study divided into two gruops they are 15 students in eksperimental class by using Make A Match (MAM) inadel and 15 students as a control class usinf conventional method.The instrument was used instrumen test. Based on analysis data, in uji deskriptif, uji normalitas , uji homogenitas and uji hypothesis Non-parametric test (Mann-Withney U-test). From Mann-Withney U-test in pretest, with significance level sig 0,025 obtained Asymp.Sig 0,916 and in posttest obtained Asymp.Sig 0,001. Keywords: Make A Match (MAM), student learning outcomes cognitive, Motivation, Elektrokimia